The extended clinical phenotype of 64 patients with dedicator of cytokinesis 8 deficiency - Engelhardt, Karin R.; Gertz, Michael E.; Keles, Sevgi; Schaeffer, Alejandro A.; Sigmund, Elena C.; Glocker, Cristina; Grimbacher, Bodo (Mosby-Elsevier, 2015)
Background: Mutations in dedicator of cytokinesis 8 (DOCK8) cause a combined immunodeficiency (CID) also classified as autosomal recessive (AR) hyper-IgE syndrome (HIES). Recognizing patients with CID/HIES is of clinical importance because of the difference in prognosis and management. Objectives: We sought to define the clinical features that distinguish DOCK8 deficiency from other forms of HIES and CIDs, study the mutational spectrum of DOCK8 deficiency, and report on the frequency of specific clinical findings. Methods: Eighty-two patients from 60 families with CID and the phenotype of AR-HIES with (64 patients) and without (18 patients) DOCK8 mutations were studied. Support vector machines were used to compare clinical data from 35 patients with DOCK8 deficiency with those from 10 patients with AR-HIES without a DOCK8 mutation and 64 patients with signal transducer and activator of transcription 3 (STAT3) mutations. Results: DOCK8-deficient patients had median IgE levels of 5201 IU, high eosinophil levels of usually at least 800/mu L (92% of patients), and low IgM levels (62%). About 20% of patients were lymphopenic, mainly because of low CD4(+) and CD8(+) T-cell counts. Fewer than half of the patients tested produced normal specific antibody responses to recall antigens. Bacterial (84%), viral (78%), and fungal (70%) infections were frequently observed. Skin abscesses (60%) and allergies (73%) were common clinical problems. In contrast to STAT3 deficiency, there were few pneumatoceles, bone fractures, and teething problems. Mortality was high (34%). A combination of 5 clinical features was helpful in distinguishing patients with DOCK8 mutations from those with STAT3 mutations. Conclusions: DOCK8 deficiency is likely in patients with severe viral infections, allergies, and/or low IgM levels who have a diagnosis of HIES plus hypereosinophilia and upper respiratory tract infections in the absence of parenchymal lung abnormalities, retained primary teeth, and minimal trauma fractures.
Keywords: Primary combined immunodeficiency; hyper-IgE syndrome; autosomal recessive hyper-IgE syndrome; dedicator of cytokinesis 8; signal transducer and activator of transcription 3; Molluscum contagiosum